Evaluation of Recombinant Type-Specific Antigens of Orientia tsutsugamushi Expressed by a Baculovirus-Insect Cell System as Antigens for Indirect Immunofluorescence Assay in the Serological Diagnosis of Scrub Typhus - Ogawa, Motohiko; Ando, Shuji; Saijo, Masayuki (Japanese Journal of Infectious Diseases, 2020)
Scrub typhus (ST) is a mite-borne rickettsiosis caused by the intracellular bacterium Orientia tsutsugamushi (OTS), which is classified as a biosafety level-3 (BSL-3) pathogen. For serological tests of ST, mouse fibroblast cells infected with the five prevalent serotypes of OTS in Japan are generally used as antigens for indirect immunofluorescence assay (IFA). In this study, Spodoptera frugiperda derived insect cell line (Sf9) cells infected with recombinant type-specific antigen (rTSA)-expressing baculovirus were used for IFA. The paired serum samples of 15 ST patients, 10 rickettsiosis patients, and 10 control individuals were used. IgM and IgG titers determined by the rTSA-based IFA were correlated with those determined by the OTS-infected cell-based IFA (R2 = 0.7319 to 0.7956). Based on the criteria for serological diagnosis, such as a suitable cutoff for single serum samples (IgM ≥ 1:160) and/or a significant increase in IgG titers between paired sera (≥ 4-fold), all 15 ST patients diagnosed as positive with the OTS-infected cell-based IFA were also diagnosed as positive by the rTSA-based IFA, whereas all 10 rickettsiosis patients and 10 control individuals were not. Thus, the rTSAs, which can be prepared in BSL-2 laboratories, are efficacious for the serological diagnosis of ST.